Relationship of Nutritional Substance toward HB Content of Chronic Kidney Failure Patients which Running Hemodialysis - Listrianah; Muzakar; Febriyanti, Enggi; Fudholi, Ahmad (International journal of engineering and advanced technology, 2019)
Chronic Renal Failure (CRF) is a disease caused due to kidney damage or deterioration glomerulus filtrate rate (GFR/GFR/Glomerular Filtration Rate) <60 ml/min /1.73 m2 for ≥ 3 months. One of the complications that often appears in CRF is anemia or decrease of hemoglobin level in the blood that is related to the relationship intake of nutrients (protein, vitamin C, folic acid and iron). The purpose of this study was to determine the relationship Intake of nutrients (protein, vitamin C, folic acid and iron) on Hb levels of chronic renal failure patients undergoing hemodialysis in RSI Siti Khadijah Palembang. This type of research is an observational analytic with a cross-sectional study design. Population in this study were all outpatients with chronic renal failure undergoing hemodialysis in RSI Siti Khadijah Palembang with total research subjects were 50 subjects, taken using purposive sampling and analyzed using chi-square test. The result showed that there are 52% of patients with chronic renal failure are male more than female. The aged 50-64 years old is 44% and 30-49 years old are 32%. The percentage of outpatients who had an adequate intake of protein, vitamin C, folic acid and iron were 28%, 10%, 0%, and 18% respectively, meanwhile, most of the patients had low hemoglobin levels which were 94%. There was not a significant association between intake of nutrients (protein, vitamin C, folic acid and iron) on Hb levels of chronic renal failure patients undergoing hemodialysis in RSI Siti Khadijah Palembang. Based on these results, should be noted again nutrient intake (protein, vitamin C, folic acid and iron) outpatient before and after undergoing hemodialysis to support the optimal outcome of hemodialysis therapy.